The clinical efficacy of lavender oil inhalation on intensity of menstrual pain from primary dysmenorrhea - Farid Zayeri; Ziba Raisi Dehkordi; Fatemeh Sadat Hosseini-Baharanchi (Shahrekord University of Medical Sciences, 2019)
Introduction: Primary dysmenorrhea is defined as painful menses with cramping sensation in the lower abdomen with normal ovulatory cycles which has no pelvic pathology. This study aimed to evaluate the effect of inhalation of Lavandula angustifolia (lavender) essential oil on alleviating primary dysmenorrhea.Methods: This randomized double-blinded clinical trial included 96 students (48 in lavender and 48 in placebo groups) from Tehran University of Medical Sciences, Tehran, Iran. Single students with regular menstrual cycles suffering from primary dysmenorrhea regarding the verbal multi-dimensional scoring system were included. The intervention group was administered to inhale lavender essential oil (diluted in sesame oil in 2:1 ratio). The control group only inhaled sesame essential oil. The visual analogue scale (VAS) was used to assess the pain score at the baseline and 1, 2, 4, and 48 hours after intervention. Generalized estimation equations method was used for data analysis.Results: The students' mean ± standard deviation (SD) age was 20.32±1.38 years. No significant difference was found in demographic and menstrual characteristics between groups. The mean VAS was not significantly different between groups at the baseline. Lavender inhalation reduced the mean±SD primary dysmenorrhea score of 2.92±0.2 according to VAS significantly during 48 first hours adjusted for baseline VAS (P < 0.001).Conclusion: It could be concluded that lavender inhalation can decrease primary dysmenorrhea. The observed effectiveness of lavender inhalation as an inexpensive therapy without evidence of adverse event supports the interest for potential application of this therapy.